Remembrance of Iqbal in Arabic Countries - Bibi, Nazia (Journal of Islamic and Religious Studies, 2016)
Allama Muhammad Iqbal became popular after the translations of his work into Arabic .Scholars, thinkers, writers, and politicians of Arabia were very much influenced by his literary works. A number of books were written on him. Other scholars and Muslim thinkers study his works with keen interest even in the modern times. The universities and other institutions in the Arabian countries have concentrated and contributed in the establishment of academic studies on various aspects of his life, literary works and different translations. This article intended to briefly cover Seminars and celebrations commemorating Iqbal in the Arab countries.